Internal Control Systems and Financial Management in Uganda: A Case of Rukungiri District Local Government. - Turyamusiima, Judith (Kabale University, 2024)
This study examined the effect of internal control systems on the financial management of Rukungiri District Local Government, Uganda. The research design was cross-sectional. Both qualitative and quantitative research design approaches were used. A sample of 138 respondents consisting of District Administration and Management staff, Internal auditors, Finance and Accounting, District Finance Committee, and Budgeting was drawn from a population of 210 study subjects using simple random sampling and purposive sampling techniques. Data was collected using a structured questionnaire and analyzed using the SPSS program. Pearson correlation was used to establish the relationship between the independent and dependent variables. The results of the study revealed that some district staff do not comply with the accounting and financial policies of the district, resulting in poor financial management practices. Some accounting officers did not follow the policies and guidelines in budget allocations for the district and hence poor accentuality of funds meant for road rehabilitation and health centers. The study results revealed that not all financial transactions had been recorded in a timely, accurate, and clear nature for every financial year which is a requirement for all public entities by the laws in Uganda. As a result, there was poor accountability on funds utilization at Bwanga stock farm with the land having no land title and some health centers having obsolete and faulty medical equipment. The findings revealed a significant strong positive relationship between the internal control system and financial management with a Pearson correlation r = 0.643 and Sig =0.000<0.01. The study concludes that a positive relationship means that an increase in the internal control systems leads to a corresponding improvement in financial management. Since the relationship is strong and significant, it can be concluded that internal controls influence financial management at Rukungiri District Local Government. Regression analysis indicates that internal control systems contribute 61.0% in influencing financial management. Therefore, the district administration should emphasize more internal control systems in financial management.